The Determinant of Training and Development, Competency Based Potential, and its Impact to Employee’s Performance at The Defense Ministry Department - Faeni, Dewi Puspaningtyas; Setiawan, Jodi; Faeni, Ratih Puspitaningtyas (International Journal of Business Studies, 2025)
Purpose of this research is to determine the effect of motivation, competency-based potential, training and development simultaneously on employee performance moderated by work experience. Research methodology being used for this study was quantitative approach, a questionnaire instrument distributed to 198 people at the Defense Ministry Department. Resulted that Motivation, Collective Motivation, Competency-Based Potential, and Training and Development have a significant effect on employee performance. Competency-Based Potential, Training and Development do not have a significant effect on employee performance. The Moderating Role of Work Experience does not moderate the relationship between motivation and performance. Limitations: This study was conducted at the Defense Ministry Department. The variables studied are related to motivation, competency-based potential, training and development on performance which is associated with the work experience variable as a moderating variable. Providing practical recommendations to improve employee performance through more effective motivation, competency development, and training and development programs.